Analysis of the ICT sector using the synthetic control method. - Přerovský, David; Frýd, Lukáš; Sokol, Ondřej; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2025)
This thesis applies the Synthetic Control Method to evaluate the causal impact of the Brexit referendum on the Science and Technology sector in the United Kingdom. Using a carefully selected set of predictors and a donor pool comprised of OECD countries, a synthetic UK is constructed to act as a counterfactual benchmark to the real UK. By comparing the two, the research shows a statistically significant negative impact on sector's Gross Value Added in the short term, with the gap stabilizing after 2020. While the long-term effect remains uncertain, the findings demonstrate that Brexit imposed a measurable economic cost—at a minimum in the short term—on the UK’s innovation economy.
Vedoucí práce: Lukáš Frýd
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: ekonometrie a operační výzkum [obor bakal. práce]; bakalářské práce; bachelor's theses